Sustainability of digital libraries: economic issues and business planning - Collier, Mel (Henry Stewart Talks, 2012)
Definitions, Types of digital library, Assemblage, Sustainability, Open access, Big deals, Repositories, Sustainability, Born digital, Digitisation, Examples, Business models, Business planning, Examples, Conclusions